ESL students' attitude towards texts and teaching methods used in literature classes. - Ghazali, Siti Norliana; Setia, Roszainora; Muthusamy, Chittra; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
Malaysia’s Vision is for the country to become a fully developed nation by 2020. In order to compete at international level, the country needs to produce future workers who are well-versed in English. The National Philosophy of Education aims to produce holistic graduates who excel academically and have better intercultural understanding, which resulted in the re-introduction of literature into the curriculum. In addition, English is also used as the medium of instruction for teaching science and mathematics. In 2000, literature became a part of the English syllabus when the Literature in English Component was implemented in secondary schools. This paper aims to discuss students’ attitudes towards the texts used in the program, the challenges faced in reading these texts and the type of texts students prefer to read. It also discusses the teaching strategies used in class, their effectiveness as well as the methods favoured by students. The study was carried out in two schools in Kemaman, Terengganu involving 110 Form Five students. Questionnaire and interview were used as the research instrument. Findings suggested that students generally had positive attitudes towards the text selection although they were less enthusiastic about the teaching methods used by teachers.